Optimisation and control of processes in apparel manufacturing : new tools for efficiency and quality assurance in industrial sewing technology - Carvalho, Helder (2010)
The industrial production of garments and similar textile end products is an activity with roots back to the 19th century that has profited immensely from continuous technological developments since its first emergence. However, several characteristics of the materials that are processed give rise to technical issues that are difficult to objectively manage and control. The machines, although often equipped with complex devices to aid in material handling, are blind regarding the process itself; they run with an initial set-up and are neither capable of adapting to varying sewing conditions nor can they detect anomalous operation. This work intends to measure and analyse several sewing variables in-process, in order to develop objective tools to plan, monitor and control the process. Several variables related to stitch formation, material feeding and needle penetration, were measured dynamically in an extensive experiment. The results found point to the possibility of designing monitoring and control algorithms for several sewing parameters, concurrently with process planning and material testing tools.